Synthesis, Analytical, Thermodynamic Studies and Uptake Behavior of: Copper and Cadmium by New Schiff-base Chelating Resins - W.S. Hanoosh (Journal of Global Pharma Technology, 2018)
The present work carried out a study on new Schiff-bases ligand derived from (P-phenyl amine and O-amino phenol) with 3-hydroxy benzaldehyde, which has been successfully prepared in warm alcoholic medium. These ligands were characterized by FTIR spectroscopy, CHN analysis & Uv-Visible spectra. From the UV –Vis spectra show that both heavy metal [Cu2+, Cd2+] form complexes with both schiff-bases in the ratio (1:2) [M: L]. Thermodynamic parameters were evaluated at different temperature using vant-hoff equation. Finally polyurethane foam from these ligand were prepared through the reaction with diisocyanate compound (MDI) and thermal study of these prepared polymers were evaluated by using thermogravemetric analysis (TGA)Keywords: Schiff-base, Polyurethane foam, TGA analysis.